Brain Morphometry and Cognitive Performance in Normal Brain Aging: Age- and Sex-Related Structural and Functional Changes - Statsenko, Yauhen; Habuza, Tetiana; Smetanina, Darya; Simiyu, Gillian Lylian; Uzianbaeva, Liaisan; Neidl-Van Gorkom, Klaus; Zaki, Nazar; Charykova, Inna; Al Koteesh, Jamal; Almansoori, Taleb M.; Belghali, Maroua; Ljubisavljevic, Milos (Frontiers in Aging Neuroscience, 2022)
Background: The human brain structure undergoes considerable changes throughout the lifespan. In analogous to this, cognitive function can be affected either negatively or positively. There are several obstacles that resist the desire of working out a precise descriptive model of normal brain aging from the accelerated one. Objective: To work out a precise descriptive model of brain structural and functional changes in normal aging. Materials and methods: By using voxel-based morphometry and lesion segmentation along with linear statistics and machine learning we analyzed structural changes of the major brain compartments and modeled dynamics of neurofunctional performance across the life. With Mann- Whitney U-test we studied sex differences in lifelong changes of brain volumetric data. We tested the hypothesis that performance in some cognitive domains might decline as a linear function of age while other domains might have a non-linear dependency to it. We correlated volumetric changes of major brain compartments with dynamics of psychophysiological performance in age groups. Then we tested linear models of structural and functional changes for significant differences between slopes in age groups with T-test. Results: White matter hyperintensities are not the major determinant of brain structural changes throughout life. They should be considered as a sign of a disease rather than a common outcome of aging. There is sex difference either in the speed or in the onset of the gray matter atrophy. It either starts earlier or goes faster in males than in females. Marked sex difference in the proportion of total CSF and iCSF justifies that elderly men are prone to age related brain atrophy much more than women of the same age. Conclusion: The article gives an indication of the conceptual structural changes in the brain compartments. The data obtained justify the presence of distinct patterns of age-related changes in cognitive functions. Cross-life slowing of decision-making may follow the linear tendency of enlargement of the interhemispheric fissure because the center of task switching and inhibitory control is allocated within the medial wall of the frontal cortex and its atrophy accounts for the expansion of the fissure